Correlation between the hemoporfin‐mediated photodynamic treatment response and the dermoscopy vascular pattern in patients with a port‐wine stain: a prospective study. (5th June 2020) - Wang, X.; Suo, H.; Gao, Y.; Du, H.; Fu, Y.; Sha, S.; Liu, Y.; Su, X.; An, X.; Guo, X.; Li, Y.; Tao, J.
Abstract: Background: Vascular targeted photodynamic therapy (PDT) is a novel and promising therapy for the treatment of port‐wine stains (PWS). There has been little prior exploration to our knowledge of how the dermatological vascular pattern may predict the response to PDT. Objectives: To analyse whether the vascular pattern classifications of PWS by dermoscopy can predict the efficacy of PDT. Methods: This prospective cohort study included 163 patients with a clinical diagnosis of PWS who were treated twice with hemoporfin‐mediated photodynamic therapy (HMME‐PDT) at two‐month intervals and followed up for 6 months. The vascular manifestations of dermoscopy with PWS were independently classified into 8 categories by 3 dermatologists. Images of the lesions were taken using VISIA, and the vascular patterns were imaged by dermoscopy by the same investigator. Images were captured before and after each treatment. The efficacy was evaluated with pre‐ and post‐treatment VISIA images, and correlations between efficacy and vascular patterns were analysed by four dermatologists in a blinded and independent manner, between 10 January 2019 and 11 December 2019. Results: In the dermoscopy images for the whole cohort, dotted and globular vessels (15.3%), short clubbed vessels (18.4%) and curved vessels (12.9%) were highly associated with cure and beneficial treatment effects. Pale halos surrounding brown dots (8.0%) and arborizing vessels (9.8%) were mainly correlated with skin lesion alleviation. Mixed vessels (12.9%), a grey‐whitish veil (11.7%) and reticular patterns (11.0%) were mainly associated with no effect. The differences between each subgroup were statistically significant ( P = 0.000). Conclusions: There is a clear correlation between the efficacy of PDT and the dermoscopy pattern in patients with PWS. Dermoscopy may therefore provide very useful clinical information prior to treatment in these cases. In addition, the vascular manifestations of PWS determined by dermoscopy help to predict response to PDT and manage patient expectations.